Honorable Mention for CNUR816: Health Assessment at Ryerson University - Ahmed, Mariam; Pirner, Diane; Koechli, Linda; Glynn, Maureen (International Journal of Emerging Technologies in Learning (iJET), 2012)
This article provides an overview of the digital learning objects created to address the need for